2015
DOI: 10.1073/pnas.1512378112
|View full text |Cite
|
Sign up to set email alerts
|

Whole-agent selectivity within the macaque face-processing system

Abstract: The primate brain contains a set of face-selective areas, which are thought to extract the rich social information that faces provide, such as emotional state and personal identity. The nature of this information raises a fundamental question about these face-selective areas: Do they respond to a face purely because of its visual attributes, or because the face embodies a larger social agent? Here, we used functional magnetic resonance imaging to determine whether the macaque face patch system exhibits a whole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 51 publications
7
35
0
Order By: Relevance
“…Functional specializations along the ventral series of face areas follow a progression similar to that in the macaque monkey, suggesting a hierarchical organization: in the occipito-temporal direction face selectivity increases (Bell et al 2009), position dependence decreases (Hemond et al 2007), mirror symmetric confusion of facial profile views emerges (Axelrod & Yovel 2012, Kietzmann et al 2012), and facial identity selectivity grows stronger (Yang, Susilo, & Duchaine, in press). Similarly, in both macaque and human face areas, the response to faces is augmented in the presence of an anatomically correctly placed body, and this augmentation grows stronger from posterior to anterior face areas (Bernstein et al 2014, Fisher & Freiwald 2015b, Song et al 2013). Furthermore selectivity for facial motion is highly pronounced in dorsal areas, but not in ventral ones (Fox et al 2009, Pitcher et al 2011a).…”
Section: Neural Systems For Face-processingmentioning
confidence: 98%
“…Functional specializations along the ventral series of face areas follow a progression similar to that in the macaque monkey, suggesting a hierarchical organization: in the occipito-temporal direction face selectivity increases (Bell et al 2009), position dependence decreases (Hemond et al 2007), mirror symmetric confusion of facial profile views emerges (Axelrod & Yovel 2012, Kietzmann et al 2012), and facial identity selectivity grows stronger (Yang, Susilo, & Duchaine, in press). Similarly, in both macaque and human face areas, the response to faces is augmented in the presence of an anatomically correctly placed body, and this augmentation grows stronger from posterior to anterior face areas (Bernstein et al 2014, Fisher & Freiwald 2015b, Song et al 2013). Furthermore selectivity for facial motion is highly pronounced in dorsal areas, but not in ventral ones (Fox et al 2009, Pitcher et al 2011a).…”
Section: Neural Systems For Face-processingmentioning
confidence: 98%
“…Brain imaging and electrophysiological experiments have shown that multiple ‘face patches’ are evident in the temporal lobe of humans, rhesus monkeys, and marmosets (Hung et al, 2015; Kanwisher et al, 1997; Tsao et al, 2008), suggesting that such a network might be a core feature of the primate social brain. Current studies are investigating specialization among such regions for extracting different types of information from faces, such as head orientation, direction of gaze, individual identity, body context, and facial motion (Fisher and Freiwald, 2015a, b; Freiwald and Tsao, 2010; Hoffman and Haxby, 2000; Leopold et al, 2006; Polosecki et al, 2013). …”
Section: Rodent and Monkey Models Of Human Social Behaviormentioning
confidence: 99%
“…Fourth, generalizing past electrophysiological findings of personal familiarity (39), which had suggested localized representations (3941), response enhancement by personal familiarity was ubiquitous within face selective areas. Thus the faces that shape face-selective cortex throughout ontogeny appear to alter all the different face representations that the face-processing system harbors (15, 17, 42). Finally, familiarity effects did not grow stronger as face representations get transformed from picture to identity-based formats from posterior to anterior IT core face areas.…”
mentioning
confidence: 99%